Wissenschaft des Judentums as a Paradigm for New Muslim Approaches to Islam (American Journal of Islam and Society, 2011)
Although Wissenschaft des Judentums was the brainchild of German Jews,it reflected the aims of European Jews in general. As noted by the late ProfessorAmos Funkenstein, “even if we grant that the majority of traditionalJews in France, Austria, and Germany were not aware of the full scopeof the achievements of the Wissenschaft, its results nevertheless faithfullyreflected the desires and self-image of nineteenth-century Jews craving foremancipation, the mood of the “perplexed of the times.”1 The period ofthe Enlightenment did little to change the lot of the Jew: he was still seenby many as a Christ-killer, his identity linked to a particular nation—andhe could, therefore, never be fully accepted as part of any other nationalentity. Although some Jews may have become totally assimilated and evenconverted to Christianity, the general perception was that the Jews wantedto be conditional citizens: while adopting the culture of the environment,they wanted to preserve their special nature as a subculture ...